Historical Overview of Taenia asiatica in Taiwan - Ooi, Hong Kean (The Korean Society for Parasitology and Tropical Medicine, 2013)
An overview of the epidemiological, biological, and clinical studies of Taenia and taeniasis in Taiwan for the past century is presented. The phenomenal observations that led to the discovery of Taenia asiatica as a new species, which differ from Taenia solium and Taenia saginata, are described. Parasitological surveys of the aborigines in Taiwan revealed a high prevalence of taeniasis, which might be due to the culture of eating raw liver of hunted wild boars. Chemotherapeutic deworming trials involving many patients with taeniasis were discussed. Praziquantel was found to be very effective, but sometimes complete worms could not be recovered from the feces after treatment, probably due to the dissolution of the proglottids. Atabrine, despite some side effects, can still be used, in properly controlled dosages, as the drug of choice for human T. asiatica infection if we need to recover the expelled worms for morphological examinations. Research results on the infection of T. asiatica eggs from Taiwan aborigines in experimental animals were also noted. Since the pig serve as the natural intermediate host of T. asiatica and the predilection site is the liver, a differential comparison of other parasitic pathogens that might cause apparently similar lesions is also presented.